Connecting microscopic structures, mesoscale assemblies, and macroscopic architectures in 3D-printed hierarchical porous covalent organic framework foams - Mohammed, Abdul Khayum; Usgaonkar, Saurabh; Kanheerampockil, Fayis; Karak, Suvendu; Halder, Arjun; Tharkar, Minakshi; Addicoat, Matthew; Ajithkumar, Thalasseril G.; Banerjee, Rahul (Journal of the American Chemical Society, 2020)
The induction of macro and mesopores into two-dimensional porous covalent organic frameworks (COFs) could enhance the exposure of the intrinsic micropores toward the pollutant environment, thereby, improving the performance. However, the challenge is to build a continuous hierarchically porous macro-architecture of crystalline organic materials in the bulk scale. In this regard, we have strategized a novel synthetic method to create hierarchically porous COF foams consisting of ordered micropores (2-2.2 nm) and disordered meso and macropores (50 nm to 200 mu m) as well as ordered macropores (1.5 mm to 2 cm). Herein, graphene oxide was used for creating disordered macro and mesopores in COF-GO foams. Considering the rheological features of the precursor hydrogel, we could integrate crystalline and porous COF-GO foams into self-supported three-dimensional (3D)-printed objects with the desired shapes and sizes. Therefore, we have engineered the 3D macro-architecture of COF-GO foams into complex geometries keeping their structural order and continuous porosity intact over a range of more than a million (10(-9) m to 10(-3) m). The interconnected 3D openings in these COF-GO foams further enhance the rapid and efficient uptake of organic and inorganic pollutants from water (>95% removal within 30 s). The abundant distribution of interconnected macroporous volume (55%) throughout the COF-GO foam matrix enhances the flow of water (1.13 x 10(-3) m.s(-1)) which results in efficient mass transport and adsorption.

Chemically gradient hydrogen-bonded organic framework crystal film - Mohammed, Abdul Khayum; Raya, Jesus; Pandikassala, Ajmal; Addicoat, Matthew A.; Gaber, Safa; Aslam, Mohamed; Ali, Liaqat; Kurungot, Sreekumar; Shetty, Dinesh (Angewandte Chemie-International Edition, 2023)
Hydrogen-bonded organic frameworks (HOFs) are ordered supramolecular solid structures, however, nothing much explored as centimetre-scale self-standing films. The fabrication of such crystals comprising self-supported films is challenging due to the limited flexibility and interaction of the crystals, and therefore studies on two-dimensional macrostructures of HOFs are limited to external supports. Herein, we introduce a novel chemical gradient strategy to fabricate a crystal-deposited HOF film on an in situ-formed covalent organic polymer film (Tam-Bdca-CGHOF). The fabricated film showed versatility in chemical bonding along its thickness from covalent to hydrogen-bonded network. The kinetic-controlled Tam-Bdca-CGHOF showed enhanced proton conductivity (8.3x10(-5) S cm(-1)) compared to its rapid kinetic analogue, Tam-Bdca-COP (2.1x10(-5) S cm(-1)), which signifies the advantage of bonding-engineering in the same system.
Keywords: Chemical Gradience; Crystal Films; Free-Standing Films; hydrogen-bonded organic framework; Interfacial Chemistry; proton conductivity